Position of Intellectual Property Rights as Banking Guarantee Based on Government Regulation Number 24 of 2022 - Lily Marlin (IHSA Institute, 2022)
The rapid development of digital technology has an impact on the growth and development of the creative economy industry where this industry is a type of industry that applies digital-based technology in its business and produces digital goods. The existence of Intellectual Property Rights attached to products owned by the Creative Economy Industry certainly requires legal protection. The facilities provided to the creative economy industry itself are IPR which can be used as collateral, but the absence of implementing regulations makes the practice still not available. This study uses a normative juridical method to analyze the existing problems. The result of this research is the issuance of PP 24 of 2022 as the implementing regulation of Law no. 24 of 2019 concerning the creative economy provides legal certainty for both debtors and creditors where this Government Regulation regulates the re-assessment of IPR as an object of debt guarantee and the availability of IPR market access as an auction place in the event of a potential default.